Implementasi Model Pembelajaran Flipped Classroom dalam Meningkatkan Kemampuan Maharah Kalam Mahasiswa - Azisi, Azisi; Nurfaiza, Nurfaiza (STAI Syaichona Moh. Cholil Bangkalan, 2024)
This study aims to evaluate the effectiveness of the Flipped Classroom model in improving the speaking skills (Maharah Kalam) of students in the Arabic Language Education Program at STAI Nurul Huda Kapongan Situbondo. The research used a quantitative approach with a quasi-experimental design, involving 30 students divided into two groups: an experimental group applying the Flipped Classroom model and a control group using conventional teaching methods. The findings indicate that the Flipped Classroom model significantly improves students' speaking skills. The t-test analysis revealed a significant difference between the two groups, with p < 0.05. Additionally, the effect size (Cohen's d) shows that Flipped Classroom has a strong impact on Maharah Kalam skills. This study also found that the model not only enhances speaking skills but also boosts students' confidence in communication. The study recommends implementing the Flipped Classroom model in Arabic language teaching to foster more interactive and effective learning.